Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Use the Distributive Property to solve the equation.

4x - 2(x - 3) = -4 + 5x - 5

show work


Sagot :

Answer:

x = 5

Step-by-step explanation:

1. Distributive Property

(Do what's in the parenthesis first)

4x - 2x + 6 = -4 + 5x - 5

2. Combine Like Terms

2x + 6 = -9 + 5x

3. Take away 6 on both sides

2x + 6 - 6 = -9 - 6 +5x

It will give u.....

2x = -15 + 5x

4. Subtract 5x on both sides

2x - 5x = -15

It will give u.....

-3x = -15

5. Divide by -3 on both sides to isolate the variable

-3x / 3 = -15/-3

Now you get....

x = 5

2 negatives make a positive

Thats ur answer

Hope this helped!